Improving Creative Thinking Problem Solving and Communication Skills of Prospective Teachers through Ethnoscience Learning in a Basic Science Concepts Course - Fine Reffiane; Dwi Hesty Kristyaningrum; Winarto Winarto (STAI Hubbulwathan Duri, 2023)
The primary issue identified in this study pertained to the suboptimal enhancement of several proficiencies, including creative thinking, problem-solving, and communication abilities, among aspiring educators. The primary objective of this research was to provide a comprehensive description and analysis of the efficacy of ethnoscience learning in enhancing the cognitive abilities of aspiring educators, specifically in the domains of creative thinking, problem-solving, and communication skills. The research design encompassed three distinct steps, specifically: 1) the collection of qualitative data, 2) the implementation of treatments, and 3) the undertaking of post-intervention qualitative investigations. A total of 120 preservice teachers in their third semester of elementary school were chosen as the sample for this study. The data was obtained by means of surveys, observations, interviews, essay examinations designed to assess creative thinking and problem-solving abilities, and observation sheets used to evaluate communication skills. The quantitative data were subjected to statistical analysis using an independent t-test and analysis of variance (ANOVA). The utilisation of ethnoscience learning has demonstrated its efficacy in enhancing cognitive abilities such as creative thinking, problem-solving, and communication skills.